A CASE STUDY OF ARGUMENT PATTERNS IN JAPAN AND KOREAN EFL LEARNERS’ ARGUMENTATIVE ESSAY - Amaliah, Amaliah; Sari, Farnia; Wahyudi, Agus (Universitas Muhammadiyah Metro, 2024)
Argumentation is crucial in education in activating students’ critical thinking and increasing their ability in thinking reflectively. TAP model as an integrated assessment framework could be used to measure their critical thinking. Thus, the aims of the study are (1) to identify the elements of the argument structures in the Japanese and Korean EFL learners’ argumentative essays, based on the (adapted) Toulmin model, (2) to evaluate the quality of the Japanese and Korean EFL learners’ argumentative writing based on the uses of the Toulmin Argument Pattern (TAP), and (3) to determine whether female and male learners have the same or different quality of argument pattern. A qualitative descriptive research design and a library research approach were carried out on this study to answer the research questions. Library research was used to collect sources and evaluate the sources taken from the ICNALE and sophisticated contrastive interlanguage analysis of Asian learners of English. The data sources were the Japanese and Korean EFL learners’ argumentative writing. Based on the quality of arguments, all students covered 1–4 levels. The highest was level 2, and the lowest was level 4. It tends to be the majority of students who are still in level 2. It needs practice to write argumentatively in order to shape the writing ability to organize a good surface structure and acceptable arguments.